Village of humans: body metaphors and indigenous social differentiation in Bolivia - Salazar, Cecilia (2006)
The social differentiation of indigenous groups, in the Andean region of Bolivia, takes place against the backdrop of the notion of "desanclaje" (disanchoring). According to this, the transit from an agrarian society to an industrial society generates in individuals a sort of "estrangement" from their local and traditional relationships of presence. This relationships are then structures at the space time intervals of modernity and capitalism through the notion of a state-nation. Education plays a key role in this process that is made visible through one of the main consequences that the differenced and unequal integration of indigenous groups to the state order entails, the social division of labor generating a separation between manual workers and intellectuals. . All these aspects are analiyzed on the basis of body metaphors that refer to the complex administration of signs and meanings under the periods of colonization and capitalism in the Andean region of Bolivia.